IMPLEMENTASI PROGRAMPREVENTIONMOTHER TO CHILD TRANSMISSION (PMTCT) DI KOTA BENGKULU TAHUN 2014 - Marleni, Wisuda Andeka (JURNAL MEDIA KESEHATAN, 2016)
Human Immunideficiency Virus (HIV) can be transmitted through a variety ofways, one is through transmission from the mother to her unborn child / mother to childtransmission (MTCT). According to the risk factors, the spread of AIDS in Indonesia January-June 2012 was dominated by heterosexuals 82.6%, 6.6% of injecting drug users, MSM asmuch as 3.6%, and 4.2% mother to child. The purpose of this research is to examine how theimplementation of the program for prevention of HIV / AIDS from mother to baby orPrevention of Mother to Child Transmission (PMTCT) in the city of Bengkulu. This researchuses the description exploratory study with a qualitative approach, conducted at the VCTclinic Hospital Dr. M.Yunus Bengkulu. Subject or primary informants in this research arepregnant women with HIV acquired the snowball technique and secondary informant astriangulation is the executive officer in the VCT clinic. The analysis showed the limitednumber of human resources for PMTCT program in RS M Yunus so it still takes energycounselors and activity funds for promotive not been allocated, in addition to the activitiesthey lead to VCT yet to PMTCT and socialization PMTCT is still within the scope of anindividual when pregnant women PLWHA consul in VCT and not run when the ANC inother health care (17 T is not already running). Based on this is expected to improve thequality of human resources and also implementing PMTCT programs for relevant agencies tosupport policies and is committed to the program and the budget allocation socializationPMTCT program to health centers in the province of Bengkulu.